2000
DOI: 10.2307/3583247
|View full text |Cite
|
Sign up to set email alerts
|

Why Do At-Risk Mothers Fail to Reach Referral Level? Barriers beyond Distance and Cost

Abstract: In southern Tanzania, few high-risk pregnancies are channeled through antenatal care to the referral level. We studied the influences that make pregnant women heed or reject referral advice. Semi-structured interviews with sixty mothers-to-be, twenty-six health workers and six key-informants to identify barriers to use of referral level were conducted. Expert-defined risk-status was found to have little influence on a woman's decision to seek hospital care. Besides well known geographical and financial barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 16 publications
10
74
0
3
Order By: Relevance
“…In agreement with previous studies, these results showed that pregnant women and other actors have ways of evaluating the risks and complications needing referral which differ from the biomedical perspective of the health workers [11,13]. The actors’ perception was that a pregnant woman who is advised to go and deliver in the hospital should go only when she has failed to deliver at the dispensary, despite being aware of the increased costs and the risk that the mother may die or have a permanent disability.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous studies, these results showed that pregnant women and other actors have ways of evaluating the risks and complications needing referral which differ from the biomedical perspective of the health workers [11,13]. The actors’ perception was that a pregnant woman who is advised to go and deliver in the hospital should go only when she has failed to deliver at the dispensary, despite being aware of the increased costs and the risk that the mother may die or have a permanent disability.…”
Section: Discussionsupporting
confidence: 92%
“…The Three Delay Model by Thaddeus and Maine [9] illustrates studies investigating barriers to adherence to referral advice for hospital delivery in rural Tanzania, including financial constraints, difficulty in accessing transport, poor quality of care and shortage of staff [5,10–12]. However, another study in southern Tanzania reported that pregnant women do not accept referral because they perceive that they will be separated from their families and fear the unfamiliar environment of the hospital [13]. Therefore, there is a need to explore the complex influences in the social environment that may prevent women in rural Tanzania adhering to the referral advice given by health workers.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the role played by religion and ethnicity in shaping women's access to maternal care, however, is beyond the scope of this paper and requires additional qualitative inquiry. A plausible explanation, to be confirmed by future research, is that both access to social networks and perceptions of the potential risks and benefits derived from using medical care differ across religious and ethnic groups [70].…”
Section: Discussionmentioning
confidence: 93%
“…The majority of the acceptors in Enugu (65%) gave convenience as the reason for accepting reduced visits [26]. Long waiting time in antenatal care clinic is associated with dissatisfaction with care [27][28][29]. An antenatal care practice that still meets the goal of antenatal care without adverse maternal or fetal outcome would save women's time.…”
Section: Discussionmentioning
confidence: 99%